Pengembangan Power Point Interaktif pada Capaian Pembelajaran Prosedur Penggunaan Alat Pelindung Diri (APD) - Myta Sabrina Wijayanti; Asrul Bahar; Ita Fatkhur Romadhoni; Sri Handajani (Journal of Creative Student Research, 2023)
This study aims to find out: 1) the results of interactive power point development on the learning outcomes of procedures for using Personal Protective Equipment (PPE); 2) the adequacy of media and interactive power point materials on procedures for using Personal Protective Equipment (PPE); 3) student responses to the results of developing interactive power point procedures for using Personal Protective Equipment (PPE). The results of the analysis of media and material feasibility data were obtained using a sheet of media and material feasibility assessment with a Likert scale. The validation sheet was assessed by UNESA PKK lecturers and Lamongan 1 State Vocational School teachers. The results of the media feasibility assessment get a value from the interpretation score scale of 91%. the results of the material feasibility assessment get a value from a 90% interpretation score scale. The results of the analysis of student response data were obtained using a questionnaire sheet with a guttman score. The questionnaire sheet was assessed by 10 students of class XI Culinary SMK Negeri 1 Lamongan. The results of the student questionnaire get a value from the interpretation score scale of 94%. In this case it shows that the development of interactive power points is stated to be very suitable for use in learning procedures for using Personal Protective Equipment (PPE).